2013
DOI: 10.1177/1088357613476344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Teacher-Implemented Video Prompting on an iPod Touch to Teach Food-Preparation Skills to High School Students With Autism Spectrum Disorders

Abstract: A multiple-probe-across-behaviors design was used to evaluate the effectiveness of video prompts delivered on an iPod Touch to teach food-preparation skills to two high school students with autism spectrum disorders (ASD) and intellectual disability. The special education teacher implemented the procedure in the high school classroom. Student data are interpreted to conclude that video prompting on an iPod Touch was effective in increasing independent performance of both students. The special education teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 18 publications
4
39
0
2
Order By: Relevance
“…e results of the current study support the findings of previous studies that video modeling is an effective instructional strategy for teaching meal preparation skills to adolescents with moderate or severe disabilities [4,5,9,10]. e present study differed from these previous studies, though, in several important ways.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…e results of the current study support the findings of previous studies that video modeling is an effective instructional strategy for teaching meal preparation skills to adolescents with moderate or severe disabilities [4,5,9,10]. e present study differed from these previous studies, though, in several important ways.…”
Section: Discussionsupporting
confidence: 85%
“…e present study differed from these previous studies, though, in several important ways. First, the tasks were more Education Research International complex and involved substantially more steps than the meal preparation tasks taught in the studies discussed previously, such as making a sandwich (12 steps) [9]; completing a math problem (10 steps) [8]; microwaving a frozen pizza or macaroni and cheese or making a smoothie (10-30 steps) [10]; preparing family packs and rst aid kits (10 steps each) [14]; and setting a table (12 steps) [11]. Furthermore, in the current study, the pizza-making task also included dishwashing and clean-up components, whereas previous studies did not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supported by Nacke & Lindley 17 who showed that 96% of the players favored their personal computer when playing games. Studies by Payne et al 18 and Johnson et al 19 indicated that the video presented on the Ipod Touch improves the skills of daily living for students with learning disabilities 20,21 . Meanwhile, a study by Palmen et al 20 indicated that using a personal digital assistant (PDA) increased the capabilities of daily routines among those with autism.…”
Section: Discussionmentioning
confidence: 99%
“…Self-monitoring can be implemented using a variety of methods including those considered more traditional, such as a paper-based method, or another option such as the use of handheld devices including iPods or cell phones (Bedesem, 2012;Blood, Johnson, Ridenour, Simmons, & Couch, 2011). Literature is replete with examples of handheld devices such as iPods, iPads, and cell phones being used to help students in P-12 settings successfully self-monitor their behaviors (e.g., Ayres, Mechling, & Sansosti, 2013;Bedesem, 2012;Gulchak, 2008;Johnson, Blood, Freeman, & Simmons, 2013;Mechling, 2007). Handheld devices are portable, easy to use, socially acceptable, and students are motivated to use them (Bauer & Ulrich, 2002).…”
Section: Self-monitoringmentioning
confidence: 99%